2012
DOI: 10.1186/1472-6882-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the aqueous extract of Senecio biafrae (Oliv. & Hiern) J. Moore on sexual maturation of immature female rat

Abstract: Background Senecio biafrae (Asteraceae) is a medicinal plant widely used by traditional healers in the western region of Cameroon for the treatment of female infertility. This experiment was designed to evaluate the effect of the aqueous extract from leaves and stems of S. biafrae (AESb) on the onset of puberty and some biochemical and physiological parameters of reproduction in immature Wistar female rats. Methods Different dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…These findings are consistent with Bayala et al (2006) and Siangcham et al (2010) who showed that estrogenic compounds induce an increase of sex glands weight, especially uterus. Indeed, estrogenic compounds cause this weight increase through mitotic activity and retention of substance in target cells, especially in uterus cell (Bayala et al, 2006;Lienou et al, 2012;Essien and …”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with Bayala et al (2006) and Siangcham et al (2010) who showed that estrogenic compounds induce an increase of sex glands weight, especially uterus. Indeed, estrogenic compounds cause this weight increase through mitotic activity and retention of substance in target cells, especially in uterus cell (Bayala et al, 2006;Lienou et al, 2012;Essien and …”
Section: Discussionmentioning
confidence: 99%
“…This interference is commonly expressed as a change in normal components of vaginal smear or disruption in the frequency of particular stages of the estrus cycle [3] . In this light, alternative treatments with plant extracts are required to have more specific pharmacological profile [4,5] . The importance of plants as a source of fertility drugs has been emphasized by many researchers [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, a large variety of studies have reported the estrogenic properties of a number of Central African medicinal plants, namely, Eryhtrina lysistemon (Fabaceae) [10,11], Brenania brieyi (Rubiaceae) [12], Millettia conraui (Leguminosae), Millettia drastica (Leguminosae), Bridelia ferruginea (Leguminosae) [13], and Erythrina poeppigiana (Fabaceae) [14,15]. A mixture of Aloe buttneri (Liliacae), Justicia insularis (Acanthaceae), Hibiscus macranthus (Malvaceae), and Dicliptera verticillata (Acanthaceae) has also been associated with estrogenic properties [16][17][18]. The body of evidence for the respective estrogenic properties and of the above-cited plants is summarized in l " Table 1.…”
mentioning
confidence: 99%
“…Concerning the study on Erythrina poeppigiana, crude methanolic and dichloromethane extracts of the stem bark of this plant induced significant estrogenic effects on some classical estrogenic targets, namely the uterus and vagina, following a three-day uterotrophic assay with ovariectomized rats (unpublished observations). Using classic chromatographic methods, five new isoflavones derivatives, namely, 5,4′-dihydroxy-7-methoxy-3′-(3methylbuten-2-yl)isoflavone, 5,2′,4′-trihydroxy-7-methoxy-5′-(3-methylbuten-2-yl)isoflavone, 5,4′-dihydroxy-7-methoxy-3′- Lienou et al [18] (3-methyl-2-hydroxybuten-3-yl)isoflavone, 3′-formyl-5,4′-dihydroxy-7-methoxyisoflavone, and 5-hydroxy-3′′-hydroxy-2′′, 2′′-dimethyldihydropyrano[5′′,6′′: 3′,4′]isoflavone, as well as six known compounds, wighteone, 3′-isoprenylgenistein, isolupabigenin, alpinumisoflavone, erypoegin D, and crystacarpin, most of which are structurally related to the soy isoflavone genistein, were isolated [14]. Ligand binding assays with estrogen receptor-α and -β revealed that isoprenyl and dimethylpyrano substituents in ring A reduced the affinity of binding to ERβ approximately 100-fold compared to genistein; the isoprenyl substituent in ring B was better accommodated, allowing 3′-isoprenylgenistein to bind with ca.…”
mentioning
confidence: 99%